The determination of the selenium levels in the blood and tissues of mice given selenium - İbrahim Pirinçci; Ahmet Ateşşahin; İzzet Karahan; İrfan Demirbaş (Eurasian Journal of Veterinary Sciences)
In this study, the selenium levels in the blood and tissue samples of mice experimentally poisoned with selenium were investigated. In the investigation, 210 mice were used. The blood and tissue samples were taken at 5, 10, 15, 30th min, 1, 2, 4, 8, 24, 48 and 72th hours following the intraperitoneal administration of selenium at the doses of 1 and 2 mg/kg. Similarly, the blood and tissue samples were taken at 30. 60 and 90th days following the oral administration ol selenium at doses of 0.5, 3 and 10 ppm. The selenium levels in the samples were spect-rophotometrically measured at 420 nm. In conclusion, the selenium levels were determined to increase depending on time and dose in mice treated with selenium orally. Whereas, when it was intraperitoneal^ given, the selenium levels were defined to reach to the maximum levels in blood at 10 and 30th min; in liver at 30th min and 2 nd hours; in kidney at 1st hour; in spleen at 15 and 30th min; in heart at 10 and 15th min; in muscle at 24 and 8th hours according to doses, respectively. Afterwards, the selenium levels were established to decrease, gradually.